2009
DOI: 10.1089/thy.2008.0102
|View full text |Cite
|
Sign up to set email alerts
|

Calculation and Validation of a Plasma Calcitonin Limit for Early Detection of Medullary Thyroid Carcinoma in Nodular Thyroid Disease

Abstract: An upper limit of 15 ng/L instead of 10 ng/L for basal pCT-C is able to detect all MTC and reduce false-positive cases. The prevalence of MTC in nodular thyroid disease in our group was approximately 1.8 per thousand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 21 publications
3
30
0
11
Order By: Relevance
“…This observation explains why men outnumbered women in the sporadic C-cell hyperplasia group by more than eightfold (66 men versus 8 women; P!0.001), whereas women predominated twofold in the occult medullary thyroid cancer group (18 women versus 8 men; Table 1). Similar gender-specific disparities have been reported elsewhere (Rink et al 2009, Scheuba et al 2009). In this study, increased basal calcitonin levels of %50 pg/ml for men were associated with much poorer positive predictive values for occult medullary thyroid cancer.…”
Section: Gender-specific Disparities In Calcitonin Secretionsupporting
confidence: 88%
See 2 more Smart Citations
“…This observation explains why men outnumbered women in the sporadic C-cell hyperplasia group by more than eightfold (66 men versus 8 women; P!0.001), whereas women predominated twofold in the occult medullary thyroid cancer group (18 women versus 8 men; Table 1). Similar gender-specific disparities have been reported elsewhere (Rink et al 2009, Scheuba et al 2009). In this study, increased basal calcitonin levels of %50 pg/ml for men were associated with much poorer positive predictive values for occult medullary thyroid cancer.…”
Section: Gender-specific Disparities In Calcitonin Secretionsupporting
confidence: 88%
“…Because male thyroids harbor more C-cells than female thyroids, serum calcitonin levels are more often higher in men than women (Heath & Sizemore 1977, Hahm et al 2001, Vierhapper et al 2005, Weinhaeusel et al 2008, Rink et al 2009, Scheuba et al 2009). This observation explains why men outnumbered women in the sporadic C-cell hyperplasia group by more than eightfold (66 men versus 8 women; P!0.001), whereas women predominated twofold in the occult medullary thyroid cancer group (18 women versus 8 men; Table 1).…”
Section: Gender-specific Disparities In Calcitonin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, several studies revealed different upper limits of basal hCT values to detect MTC and to reduce false-positive cases (12)(13)(14)(15). The present study sheds further light on the hCT measurement and its testing after pentagastrin stimulation in patients with thyroid nodule disease.…”
Section: Introductionmentioning
confidence: 54%
“…In contrast, PPV of stimulated sCT > 100 pg/mL is controversial. Although some studies reported PPV of 100% (8,10,20), many series found a value of only 25% (21), 20% (22), and 0/13 (9) in patients with elevated basal sCT, but < 100 pg/mL, who converted to levels > 100 pg/mL after stimulation. As a consequence, different cutoffs of stimulated sCT have been proposed in the literature (11)(12)(13)15,19), and this value remains undefined.…”
Section: Discussionmentioning
confidence: 99%